Zagłada i gwiazdy. Przeszłość w prozie Stanisława Lema - Gajewska, Agnieszka (Wydawnictwo Naukowe UAM, 2016)
The monograph Holocaust and the Stars. The past in the prose of Stanisław Lem links the work of the writer of His Master’s Voice with the main currents in Polish post-war prose, including the Columbus generation, the prose of minor realism, pacifistic prose, and the intellectual ‘coming to terms’ with the past. Leaving aside the futuristic visions, philosophical history and discussions of enlightenment, the author of this book concentrates on those strands that concern twentieth-century history, alluding to specific historical events and life experiences. In this book, devoted to the traces of the Holocaust of the Jews of Lviv that can be found in Stanisław Lem’s prose, the historical context covers the period from the nineteenth century, when the Polonisation of the Galician Jews began, up to the 1970s, when the writer was put under surveillance by the secret police. The background for the interpretation of Lem’s realist and science fiction novels also includes hitherto unknown facts from the writer’s biography. Thanks to extensive archival research, additional knowledge has been gained about the interwar and wartime experiences of Lem’s family, and several errors commonly appearing in his biographies have been corrected.

Książka Zagłada i gwiazdy jest poświęcona twórczości Stanisława Lema. Poszczególne interpretacje utworów odniesione zostają do wydarzeń historycznych, głównie do XX wieku. We wstępnej części książki wyjaśniam podstawowe dla moich rozważań pojęcia, sytuując je wobec dotychczasowej recepcji jego prozy. W trzech kolejnych rozdziałach skupiam się natomiast na interpretacji prozy autora Solaris przez pryzmat dziejów Lwowa, wątków autobiograficznych oraz pozycji świadka i ocalonego. W pierwszej części książki analizuję ślady historii Żydów lwowskich obecne w trylogii Czas nieutracony oraz Wysokim Zamku. W drugiej przedstawiam wątki autobiograficzne prześwitujące przez życiorysy kilku protagonistów prozy Lema, a w trzeciej odsłaniam blizny dwudziestowiecznej historii, które naznaczyły jego prozę science fiction.
Holocaust and the Stars. The past in the prose of Stanisław Lem
Keywords: Stanisław Lem; Zagłada; Żydzi lwowscy; autobiografizm